Treatment for Severe Lupus Nephritis: A Cost-Effectiveness Analysis in China - Dai, Zonglin; Zhang, Xi; Wong, Irene OL; Lau, Eric HY; Lin, Zhiming (Frontiers in Pharmacology, 2021)
Background Lupus nephritis (LN) is the most common secondary glomerular diseases that will cause end-stage renal disease (ESRD) and renal-related death. The cost-effectiveness of various treatments for LN recommended by official guidelines has not been investigated in China. Our study is to evaluate clinical prognosis and cost-effectiveness of the current treatments for severe LN. Methods A Markov model was simulated for 1,000 LN patients of 30 years old, over a 3-year and 30-year lifetime horizon respectively. We assessed the cost-effectiveness of six therapeutic strategies from a societal perspective, with cyclophosphamide (CYC) or mycophenolate mofetil (MMF) induction therapy followed by CYC, MMF or azathioprine (AZA) maintenance therapy. Main outcomes included quality-adjusted life years (QALYs), incremental cost-effectiveness ratio (ICER) and clinical prognosis. One and three times gross domestic product (GDP) per capita were used as the willingness-to-pay (WTP) thresholds. We also carried out sensitivity analysis under a lifetime horizon. Results Compared with the baseline strategy of CYC induction and maintenance, for a 3-year horizon the most cost-effective strategy was CYC induction and AZA maintenance with $448 per QALY gained, followed by MMF induction and AZA maintenance which however was not cost-effective under the one times GDP per capita WTP threshold. For a lifetime horizon, CYC induction and AZA maintenance remained the most cost-effective strategy but MMF induction and maintenance became cost-effective under the one times GDP per capita WTP threshold and achieved a higher complete remission rate (57.2% versus 48.9%) and lower risks of ESRD (3.3% versus 5.8%) and all-cause mortality (36.0% versus 40.8%). The risk of developing ESRD during maintenance was the most influential parameter affecting ICER. Conclusions The strategy of CYC induction followed by AZA maintenance was the most cost-effective strategy in China for short-term treatment, while the strategy of MMF in both induction and maintenance became cost-effective and yielded more desirable clinical outcomes for lifetime treatment. The uncertainty analysis supported the need for monitoring the progression to ESRD.